Corpus and sociolinguistics : investigating age and gender in female talk - Murphy, Bróna (Studies in corpus linguistics ;, 2010)
Age is by far the most underdeveloped of the sociolinguistic variables in terms of research literature. To-date, research on age has been patchy and has generally focused on the early life-stages such as childhood and adolescence, ignoring, for the most part, healthy adulthood as a stage worthy of scrutiny. This book examines the discourse of adulthood and accounts for sociolinguistic variation, with regards to age and gender, through the exploration of a 90,000 word age-and gender-differentiated spoken corpus of Irish English. The book explores both the distribution and use of a number of hig.